Photographs of Potter Cove, King George Island, looking northeast towards glacier in 2025 - Diego R Gómez Izquierdo; Maria Liliana Quartino (PANGAEA, 2025)
The dataset contains the photos of Potter Cove, taken near Carlini Base in 2025. Camera: Panasonic, WV-S1531L positioned at the rear entrance of Dallmann laboratory at Jubany Station. Distance between posts is approximately 4.5 m. Picture series was started in 2019 and documents ice cover in the bay, glacier front and cloud cover of the sky. Size of images: 2048 x 1536 pixel. Format of the photos is JPG.